2018
DOI: 10.1016/j.mayocp.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Disease and Venous Thromboembolism Among Patients With Incident ANCA-Associated Vasculitis: A 20-Year Population-Based Cohort Study

Abstract: Objectives To assess the cardiovascular disease (CVD) and venous thromboembolism (VTE) risks among patients with newly diagnosed ANCA-associated vasculitis (AAV). Patients and Methods A population-based incident AAV cohort of 58 patients diagnosed between 1996 and 2015 in Olmsted County (Minnesota, USA) was identified by medical record review. For each patient, 3 age- and sex-matched non-AAV comparators were randomly selected from the same population and assigned an index date corresponding to the AAV incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 43 publications
2
58
0
2
Order By: Relevance
“…Analysis of a randomized controlled trial that included patients with GPA enrolled in the Wegener's Granulomatosis Etanercept Trial (WGET) demonstrated an incidence of VTE of 7.0 per 100 person‐years . An increased likelihood of VTE was reported in a population‐based incident AAV cohort, which was driven by a significantly increased risk of developing deep venous thrombosis (DVT) . Analysis of a large cohort of patients with eosinophilic granulomatosis with polyangiitis (EGPA), GPA, and MPA demonstrated occurrence of VTE in 8.2%, 8.0%, and 7.8% of patients, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of a randomized controlled trial that included patients with GPA enrolled in the Wegener's Granulomatosis Etanercept Trial (WGET) demonstrated an incidence of VTE of 7.0 per 100 person‐years . An increased likelihood of VTE was reported in a population‐based incident AAV cohort, which was driven by a significantly increased risk of developing deep venous thrombosis (DVT) . Analysis of a large cohort of patients with eosinophilic granulomatosis with polyangiitis (EGPA), GPA, and MPA demonstrated occurrence of VTE in 8.2%, 8.0%, and 7.8% of patients, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the investigation, it should be noted that except for relapse of AAV, Mets could increase the risks of all-cause mortality [28], chronic kidney disease or ESRD [29], CVA [30] and CVD [28,31,32] in both AAV patients and the general population with MetS. In addition, AAV itself without MetS also could increase the risk for CVD compared to healthy people [14,33]. Therefore, it should not be ignored that both AAV entity and the crosssectional MetS at diagnosis may be simultaneously engaged in CVD occurrence in AAV patients: MetS might significantly initiate CVD occurrence and AAV might accelerate it.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the knowledge that patients with CIDs are at increased risk of developing CVDs, several studies have demonstrated that the risk of CVDs is heightened in AAV patients. A long-term populationbased study revealed that the risk of CVD and CVA in AAV patients were 3-and 8-fold higher than those in matched subjects [22]. In addition, a retrospective study that was performed in the United Kingdom has shown that AAV patients have high incidence of arterial and venous thrombosis [23].…”
Section: Discussionmentioning
confidence: 99%